The effect of 14 weeks of vitamin D3 supplementation on antimicrobial peptides and proteins in athletes - He, C.-S.; Fraser, W. D.; Tang, J.; Brown, K.; Renwick, S.; Rudland-Thomas, R.; Teah, J.; Tanqueray, E.; Gleeson, M. (Journal of Sports Sciences, 2016)
Heavy training is associated with increased respiratory infection risk and antimicrobial proteins are important in defence against oral and respiratory tract infections. We examined the effect of 14 weeks of vitamin D3 supplementation (5000 IU/day) on the resting plasma cathelicidin concentration and the salivary secretion rates of secretory immunoglobulin A (SIgA), cathelicidin, lactoferrin and lysozyme in athletes during a winter training period. Blood and saliva were obtained at the start of the study from 39 healthy men who were randomly allocated to vitamin D3 supplement or placebo. Blood samples were also collected at the end of the study; saliva samples were collected after 7 and 14 weeks. Plasma total 25(OH)D concentration increased by 130% in the vitamin D3 group and decreased by 43% in the placebo group (both P = 0.001). The percentage change of plasma cathelicidin concentration in the vitamin D3 group was higher than in the placebo group (P = 0.025). Only in the vitamin D3 group, the saliva SIgA and cathelicidin secretion rates increased over time (both P = 0.03). A daily 5000 IU vitamin D3 supplement has a beneficial effect in up-regulating the expression of SIgA and cathelicidin in athletes during a winter training period, which could improve resistance to respiratory infections.